Non-linear camera calibration for 3D reconstruction using straight line plane object - Silvatti, A.; Rossi, M.; Dias, F.; Leite, N.; Barros, R. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
One critical aspect to 3D reconstruction of human motion using videogrammetry is related to the need for an accurate calibration of large volumes. Most of calibration methods used in biomechanics requires the construction, transportation and measurement of rigid structures and this is more difficult when larger volumes are involved. Recently, alternative approaches have been proposed to overcome this critical aspect (Cerveri et al., 1998; Zhang, 2000). This work presents preliminary results of the proposition and evaluation of a non-linear camera calibration method for 3D reconstruction using a plane object containing straight lines.